KOMBINASI HUKUM ISLAM DAN NEGARA MENJADI PELINDUNG KORBAN DALAM MENYIKAPI KEKERASAN DALAM RUMAH TANGGA (KDRT) - Ajjahidi, Muhammad Hilmi (El-Ahli : Jurnal Hukum Keluarga Islam, 2022)
The family is an important instrument in the life of every human being. But not infrequently also in going out will not always go smoothly, often there will be a fight that can sometimes lead to domestic violence. Domestic violence is a form of criminal offense because it causes harm both physically and psychologically to the victim who experiences it. And the motives that result in domestic violence vary, including due to economic problems, uneventful communication between husband and wife which results in disharmony in the family and so on. In this case, Islam and the state provide ways and guidance in carrying out life in the household, when domestic violence occurs, Islam provides protection in its teachings and the state also provides guidance and protection in its laws. This study uses normative juridical research, where the method examines laws that rely on library materials or secondary data, and the data collection techniques use library research by studying a number of laws and regulations, books and literature that are related to the theme of this article.